Childhood nephritic syndrome Clinical manifestations and histopathlogical spectrum - Ahmed, Nariman F.; Ibrahim, Raghad (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Nephrotic syndrome in children is a clinical manifestation of different histopathological subtypes. Objectives: The objectives were to study the different histopathological subtypes of idiopathic nephrotic syndrome and to study their clinical and biochemical parameters at the time of diagnosis for children admitted to Children Welfare Teaching Hospital. Methods: A Retrospective study M’as done on 160 children with idiopathic nephrotic syndrome who were diagnosed and/or treated at Children Welfare Teaching Hospital and were followed up in the pediatric nephrology consultation clinic betM’een April 2004 and April 2006. Results: The study group included 40 children with idiopathic nephrotic syndrome r Who underwent renal biopsy. There were 26(68.7%) males and 14(31.2%) females. Age at onset ranged between (1-15) years, median age (3.5) years. Facial oedema M’as fcnmd in 90%, hypertension in 45% patients, gross hematuria in 27.5 and persistent microhematuria in 45%. Sixteen (40%) patients had focal and segmental glomemlosclerosis on renal biopsy, nine (22.5%) patients minimal change nephrotic syndrome, eight (20%) patients mesangioproliferative glomerulonephritis, and seven (17.5%) patients had membranoproliferative glomerulonephritis. Conclusion: Focal and segmental glomemlosclerosis was the most common histopathological subtype in our study group. Further large studies is needed to find out changing trends of histopathology in childhood nephrotic syndrome